The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/hyp.13131
|View full text |Cite
|
Sign up to set email alerts
|

Storage in confined aquifer: Spectral analysis of groundwater in responses to Earth tides and barometric effect

Abstract: Dilatation of aquifer and associated water level fluctuation in groundwater well is known to be driven periodically from lunar, solar, or other tidal forces. Time‐dependent variables in groundwater system, such as water level, can be converted to power spectra in the frequency domain using Fourier transform to evaluate significant fluctuation. The major innovation of this research is to develop spectral representation in frequency domain for the groundwater system that the storage in confined aquifer can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The investigation performed by Xiao et al showed that the average decline rate of groundwater level during 2007-2013 was higher than during 2001-2006 in Beijing piedmont plain and the decline rate of groundwater level in the agricultural irrigation areas was lowest, compared with those in residential and industrial areas [19]. In addition, it was found that the dynamic change in groundwater level was usually of extremely complex nonlinear characteristics, such as periodicity and randomness [20]. Moreover, some influencing factors, e.g., rainfall and irrigation amount, vary periodically [21].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation performed by Xiao et al showed that the average decline rate of groundwater level during 2007-2013 was higher than during 2001-2006 in Beijing piedmont plain and the decline rate of groundwater level in the agricultural irrigation areas was lowest, compared with those in residential and industrial areas [19]. In addition, it was found that the dynamic change in groundwater level was usually of extremely complex nonlinear characteristics, such as periodicity and randomness [20]. Moreover, some influencing factors, e.g., rainfall and irrigation amount, vary periodically [21].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a great number of researchers try to put forward the relationship between earthquakes, groundwater levels, and chemistry in different situations by field observations and scientific studies especially (Wang et al, 2001;Sneed et al, 2003;Kitagawa et al, 2006;La Vigna et al, 2012;Shi and Wang, 2014;Manga and Wang, 2015;He and Singh, 2019;Lee et al, 2020;Senthilkumar et al, 2020). Effects of the earthquakes on groundwater response vary under the control of the aquifer with the factors such as lithology, hydrogeochemistry, permeability, porosity, pore pressure change, aquifer type, barometric pressure, tidal effects, fault zones, well properties, and earthquake characteristics (Bredehoeft, 1967;Roeloffs, 1988;Brodsky et al, 2003;Claesson et al, 2004;Falcone et al, 2012;Shi et al, 2015;Rutter et al, 2016;Yan et al, 2016;Liu et al, 2018;Petitta et al, 2018;Shih, 2018;Sun et al, 2019;Lee et al, 2020;Senthilkumar et al, 2020). When the waterrock interactions occurring in the groundwater aquifer system are examined, opened/closed cracks and fault planes, deformation by co-seismic strain and post-seismic hydrogeological conditions can be considered as primary controllers (Pasvanoglu et al, 2004;Charmoille et al, 2005;Skelton et al, 2008;Reddy et al, 2011;Woith et al, 2013;Skelton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in groundwater level differ according to the aquifer type (confined or unconfined aquifer), as well as due to external stresses such as barometric pressure, precipitation, tidal effects, and earthquakes (Bredehoeft 1967;Weeks 1979;Roeloffs 1988;Healy and Cook 2002;Pacheco and Fallico 2015). Spectral analysis of groundwater level show different signal components for unconfined and confined aquifers (Rahi and Halihan 2013;Shih 2018). Groundwater levels have been used as indicators of crustal stress/strain (e.g.…”
Section: Introductionmentioning
confidence: 99%